2019
DOI: 10.3390/rs11030234
|View full text |Cite
|
Sign up to set email alerts
|

Weakly Coupled Ocean–Atmosphere Data Assimilation in the ECMWF NWP System

Abstract: Numerical weather prediction models are including an increasing number of components of the Earth system. In particular, every forecast now issued by the European Centre for Medium-Range Weather Forecasts (ECMWF) runs with a 3D ocean model and a sea ice model below the atmosphere. Initialisation of different components using different methods and on different timescales can lead to inconsistencies when they are combined in the full system. Historically, the methods for initialising the ocean and the atmosphere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(71 citation statements)
references
References 26 publications
1
70
0
Order By: Relevance
“…and the perturbed one at a given time, δx t . Provided that this perturbation is sufficiently small, its dynamics can be described by the linearised equation, dδx dt = ∂f ∂x |xt δx (8) and the formal solution can be written as,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…and the perturbed one at a given time, δx t . Provided that this perturbation is sufficiently small, its dynamics can be described by the linearised equation, dδx dt = ∂f ∂x |xt δx (8) and the formal solution can be written as,…”
Section: Resultsmentioning
confidence: 99%
“…complete sCDA) and the implicit coupling in the incremental 4DVar has shown that for long assimilation window the latter produces accurate analysis, but the explicit coupling is preferable for short assimilation windows. The transition from a reanalysis to real time prediction is currently under study [8].…”
Section: Coupled Data Assimilation In the Geosciences: Brief Surveymentioning
confidence: 99%
“…In June and July, most (93%) of the L3 SST data in the coastal region of the Southeastern YS were assigned as low, bad or worst quality data (Table 6), which resulted in the interpolation of SST data in the coastal region during the production of the L4 gridded SST datasets. The missing SST data in the coastal region were not interpolated from the nearby grid points but they were interpolated using the offshore observation data far away (10-70 km) in warm water and the climatology based on Equationa (3) and (4).…”
Section: Background and Covariances Used For The Optimal Interpolationmentioning
confidence: 99%
“…Sea surface temperature (SST) is one of the main physical variables that provides information regarding the current state of the ocean [1]. SST data have been used for data assimilation in ocean circulation models and as a bottom boundary condition for atmospheric prediction models [2][3][4]. They are also essential for climate modeling and ocean-atmosphere interaction studies [5].…”
Section: Introductionmentioning
confidence: 99%
“…The turbulent surface heat and momentum fluxes are parameterized using stability functions described in Delage and Girard (1992) and Delage (1997). The DA method is a hybrid four-dimensional ensemblevariational (4D-EnVar) (Buehner et al, 2013(Buehner et al, , 2015 using incremental analysis update (IAU) initialization (Bloom et al, 1996). The IAU implementation used with the GDPS system is illustrated in Fig.…”
Section: Atmospheric Data Assimilationmentioning
confidence: 99%